V 367 CYGNI - Menchenkova, E. V. (Одеські астрономічні публікації, 2017)
The spectral and photometric investigations of the W Set-type star V 367 Cyg have been carried out. The comparison of the observed parameters of the stellar components of the system V 367 Cyg with the theoretical ones for the main-sequence stars of the same mass has shown the considerable excesses of the radii and luminosities of both components of the system. The whole complex of the observed characteristics of the bright (at present less massive: M1 = 2.3 M o ) component is well described by the current evolution theory of close binary systems of medium mass. At the same time, it is shown that the luminosity of the secondary component cannot be explained within the framework of the disc accretion model, suggested by Plavec (198oa)to describe the observed properties of W Ser-type stars.